Lost daughters - Monroe, Mary (Kensington Pub. Corp., 2013)
When her new husband Mel and her daughter Lorretta, an aspiring model, run off together, claiming they are in love, Maureen Montgomery must confront her tragic past to find the strength to overcome this devastating betrayal and make a new life for herself that is all her own.